Awareness about Female Cancers among Female Healthcare Workers and School Teachers in Tobruk, Libya: A Knowledge, Attitude, and Practice Study - Vinay Rao; Prasanna Lakshmi Rao (Journal of Public Health and Primary Care)
Background: Female cancers, such as breast, ovarian, cervical, and endometrial cancers, are major global health issues due to their prevalence and the challenges in early detection and treatment, particularly in developing regions. This study investigates the awareness and attitudes toward female cancers among healthcare workers and school teachers in the city, with a focus on how literacy affects cervical cancer screening rates. Subjects and Methods: A cross-sectional knowledge, attitude, and practice (KAP) study was conducted among working women in the city using a pretested close-ended self-administered questionnaire in the month of April 2024. Results: Significant differences in cancer KAP were observed between healthcare workers and schoolteachers. Healthcare workers had a higher awareness that obesity increases breast cancer risk (71% vs. 45%). Both groups showed a good understanding of the hereditary nature and mortality risk of breast cancer. Positive attitudes toward cancer prevention were common, yet actual preventive practices, such as human papillomavirus vaccination and monthly breast self-examinations, were low across all groups. Conclusions: The level of cancer awareness was fairly good among working women which reflected their educational status. Attitude and practice varied among the different occupations which did not correlate to educational level.